Clinical significance of ictal magnetoencephalography in patients undergoing epilepsy surgery. (January 2023) - Katagiri, Masaya; Wang, Z. Irene; Hirfanoglu, Tugba; Aldosari, Mubarak M.; Aung, Thandar; Wang, Shan; Kobayashi, Katsuya; Bulacio, Juan; Bingaman, William; Najm, Imad M.; Alexopoulos, Andreas V.; Burgess, Richard C.
Highlights: Resection should include ictal single equivalent current dipole (SECD), interictal SECD and MRI lesion localization, when feasible. Concordant ictal and interictal SECDs can be a favorable predictor of seizure freedom if the areas can be safely resected. Among SECD, dynamic statistical parametric mapping, and linearly constrained minimum variance, SECD should be considered the first line of analysis for ictal MEG when the data is amenable to SECD source localization. Abstract: Objective: The significance of ictal magnetoencephalography (MEG) is not well appreciated. We evaluated the relationships between ictal MEG, MRI, intracranial electroencephalography (ICEEG), surgery and postoperative seizure outcome. Methods: A total of 45 patients (46 cases) with ictal MEG who underwent epilepsy surgery was included. We examined the localization of each modality, surgical resection area and seizure freedom after surgery. Results: Twenty-one (45.7%) out of 46 cases were seizure-free at more than 6 months follow-up. Median duration of postoperative follow-up was 16.5 months. The patients in whom ictal, interictal single equivalent current dipole (SECD) and MRI lesion localization were completely included in the resection had a higher chance of being seizure-free significantly ( p < 0.05). Concordance between ictal and interictal SECD localizations was significantly associated with seizure-freedom. Concordance between MRI lesion and ictal SECD, concordance between ictal ICEEG and ictal and interictal SECD, as well as concordance between ictal ICEEG and MRI lesion were significantly associated with seizure freedom. Conclusions: Ictal MEG can contribute useful information for delineating the resection area in epilepsy surgery. Significance: Resection should include ictal, interictal SECDs and MRI lesion localization, when feasible. Concordant ictal and interictal SECDs on MEG can be a favorable predictor of seizure freedom.